The ramifications of human rights and fundamental freedoms: A philosophical and jurisprudential survey of classical principles - Singh, Jai S. (2011)
Human rights are universal, inalienable and sacred. They are necessary to protect the freedom, liberty and dignity of the person and to develop, mental, moral and spiritual values. In other words, human rights are essential for fullest development of the personality of human beings. Therefore, they must be protected, enriched, developed and be made available to all individuals. This article gives an overview of universalisation of human rights and fundamental freedoms. An attempt has been made to study the concept of human rights and fundamental freedoms provided in the Universal Declaration of Human Rights, 1948, International Convenant on Civil and Political Rights, 1966 and International Convenant on Economic, Social and Cultural Rights, 1966. It has also been discussed that how far and to what extent the philosophy of human rights and fundamental freedoms under the Constitution of India has been worked upon by way of different propositions. - Reproduced.
Keywords: Human rights